A calcium optimum for cytotoxic T lymphocyte and natural killer cell cytotoxicity. (July 2021) - Kaschek, Lea; Zöphel, Sylvia; Knörck, Arne; Hoth, Markus
Abstract: Cytotoxic T lymphocytes (CTL) and natural killer (NK) cells are required for host defense. They destroy malignant target cells like cancer cells. Among metal cations, Ca 2+ plays a prescinded role for CTL and NK cytotoxicity as it is the only cation used as ubiquitous second messenger. Measuring intracellular Ca 2+ concentrations [Ca 2+ ]int in single cells has greatly changed our understanding of Ca 2+ signaling. Yet, comparing the role of Ca 2+ in the pre-[Ca 2+ ]int and [Ca 2+ ]int measurement era reveals that even in the pre-[Ca 2+ ]int measurement era (before 1980), the functions of Ca 2+ and some other metal cations for the cytotoxic immune response were well established. It was even shown that Ca 2+ influx across the plasma membrane but not Ca 2+ release from intracellular sources is relevant for lymphocyte cytotoxicity and that very little Ca 2+ is needed for efficient lymphocyte cytotoxicity against cancer cells. In the [Ca 2+ ]int measurement era after 1980, many of the important findings were better and more quantitatively refined and in addition the molecules important for Ca 2+ transport were defined. The unexpected finding that there is a Ca 2+ optimum of CTL and NK cell cytotoxicity deserves some attention and may be important for anti-cancer therapy. Graphical Abstract: ga1 Highlights: Ca 2+ influx through CRAC/Orai channels is needed for optimal host defense. CTL and NK cells only require low Ca 2+ to exert cytotoxicity against cancer cells. A Ca 2+ optimum for CTL and NK cell cytotoxicity exists. CRAC/Orai channel inhibitors may improve CTL and NK cell cytotoxicity.